Development of New Ion and Plasma Surface Modification Methods; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Ryabchikov A. I. Aleksandr Ilyich (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen